1997
DOI: 10.1203/00006450-199703000-00024
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium Sulfate after Transient Hypoxia-Ischemia Fails to Prevent Delayed Cerebral Energy Failure in the Newborn Piglet

Abstract: Severely birth-asphyxiated human infants develop delayed ("secondary") cerebral energy failure, which carries a poor prognosis, during the first few days of life. This study tested the hypothesis that i.v. magnesium sulfate (MgSO4) after severe transient cerebral hypoxia-ischemia decreases the severity of delayed energy failure in the newborn piglet. Twelve piglets underwent temporary occlusion of the common carotid arteries and hypoxemia. Resuscitation was started when cerebral [phosphocreatine (PCr)]/[inorga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
42
2
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(51 citation statements)
references
References 18 publications
6
42
2
1
Order By: Relevance
“…Magnesium administration either before or after HI, ischemia, or excitotoxic exposure in perinatal and adult rats ameliorated the extent of neurologic injury (38 -43). In contrast, systemic magnesium administration after HI in newborn piglets did not prevent the development of delayed energy failure, but much lower [Mg] plasma were achieved compared with the present study (44). Furthermore, systemic magnesium administration after asphyxia in fetal sheep did not reduce the extent of cytotoxic edema, did not improve the recovery of the EEG, and did not alter the histologic outcome (45).…”
contrasting
confidence: 47%
“…Magnesium administration either before or after HI, ischemia, or excitotoxic exposure in perinatal and adult rats ameliorated the extent of neurologic injury (38 -43). In contrast, systemic magnesium administration after HI in newborn piglets did not prevent the development of delayed energy failure, but much lower [Mg] plasma were achieved compared with the present study (44). Furthermore, systemic magnesium administration after asphyxia in fetal sheep did not reduce the extent of cytotoxic edema, did not improve the recovery of the EEG, and did not alter the histologic outcome (45).…”
contrasting
confidence: 47%
“…Previous results from this study demonstrated that administration of MgSO 4 failed to reduce the delayed decline in cerebral energy metabolism after HI in newborn piglets (9). However, from the apparent success of MgSO 4 in protection against cortical injury induced by glutamate agonists (10), we surmised that local neuroprotective effects might also be expected in cerebral HI, even if global energy metabolism was unaffected.…”
mentioning
confidence: 43%
“…The physiologic, MRS, and blood [Mg 2ϩ ] results have been published previously (9). In brief, there were no significant differences between the two groups of piglets for observations of a wide range of systemic and biochemical variables, including arterial PO 2 , PCO 2 , pH, base excess, hematocrit, blood glucose, mean arterial blood pressure, heart rate, rectal and tympanic temperatures, and plasma Na ϩ , K ϩ , urea, creatinine, and lactate, either at baseline, at the end of the insult, or 2, 24, and 48 h after resuscitation.…”
Section: Physiologic and Mrs Variablesmentioning
confidence: 99%
“…150 In a further study in newborn piglets, Greenwood et al151 reported that following hypoxic -ischaemia there was no difference in the severity of cerebral damage between piglets treated with magnesium sulphate and the placebo group.…”
Section: Magnesiummentioning
confidence: 99%